Coaching millennial entrepreneurs in tourism industry: a glimpse of political skill / Melissa Wee … [et al.] - Wee, Melissa; Ahmad, Noor Hazlina; Sadik, Mohd Zaki; Abd Razak, Noraznira (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2019)
The main objective of this study is to determine whether coaching support plays a significant role towards millennial entrepreneurs’ political skill. It has been argued that political skill is a learned behavior that can be developed through various ways such as coaching, mentoring and role modelling which involves experience development. In achieving high political skill, there is a need to work with skillful coaches in order to provide successful mentorship. Since political skill is treated as multidimensional which are networking ability, interpersonal influence, social astuteness and apparent sincerity, four hypotheses were postulated in this study. This study applies Partial Least Squared method in analyzing the data that were distributed to 200 respondents through questionnaires. The findings of this study are that coaching support has positive relationships with networking ability, social astuteness and apparent sincerity. Only, interpersonal influence has a negative influence by coaching support.